EP1352 Inguinofemoral lymphadenectomy and femoral dissection: cadaveric educational video. (1st November 2019) - Selcuk, I; Akdemir Aktas, H; Ersak, B; Tatar, I; Sargon, M; Gungor, T
Abstract : Introduction/Background: Vulvar cancer is rarely seen Methodology: This step by step cadaveric educational video was recorded on the left groin. Results: Between the anterior superior iliac spine and pubic tubercle the skin incision is performed, 8 cm in length, and 2 cm below and parallel to the inguinal ligament. After the incision, dissection deepens to identify the Camper's fascia over the Scarpa's fascia. Identification and preservation of the Camper's fascia is critical in securing the skin flap and preventing skin necrosis. To dissect the fibrofatty tissue containing the superficial inguinal lymph nodes between the Camper's fascia and fascia lata; firstly, the fibrofatty tissue is mobilized under the Scarpa's fascia and dissected 2 cm cephalad to the inguinal ligament where the aponeurosis of external iliac muscle is seen. Afterwards, excision of the lymphatic and fibrofatty tissue is performed from lateral (superficial circumflex iliac vein) to medial (superficial external pudendal vein) and superior to inferior (inferomedial end of inguinal ligament where it intersects with the adductor longus muscle). The fossa ovalis is encountered after resection of superficial inguinal lymph nodes. Medial to the falciform edge of fossa ovalis, dissection of the cribriform fascia will lead to the deep inguinal lymph nodes which are located medial to the femoral vein. Great saphenous vein enters the femoral vein from the opening of fossa ovalis, so a careful dissection is needed while removing the cribriform fascia. Lymphadenectomy is performed towards the apex of femoral triangle, and there is no need to dissect the femoral sheath to excise the deep inguinal nodes completely. Finally, Cloquet's lymph node which is the most superior of deep inguinal nodes could be resected from the femoral canal under the level of inguinal ligament. Conclusion: Proper anatomical knowledge of inguinofemoral anatomy, the superficial fascia structures and deep vessel structures facilitates the inguinofemoral lymphadenectomy procedure. Disclosure: Nothing to disclose